Electric Field‐Induced Phase Transition Behaviors, Thermal Depolarization, and Enhanced Pyroelectric Properties of (Pb0.97La0.02)(ZrxSn0.89−xTi0.11)O3 Ceramics. Issue 6 (14th March 2016) - Zhuo, Fangping; Li, Qiang; Gao, Jinghan; Wang, Yujie; Yan, Qingfeng; Zhang, Yiling; Chu, Xiangcheng
Abstract : (Pb0.97 La0.02 )(Zr x Sn0.89− x Ti0.11 )O3 ( x = 0.60, 0.62, 0.64, 0.66, 0.68, 0.70, 0.72, and 0.74) ceramics with the compositions in tetragonal antiferroelectric (AFE) region, near the morphotropic phase boundary, were prepared by using the conventional solid‐state reaction process. Their electric field‐induced phase transitional behaviors, composition‐ and temperature‐dependent dielectric, depolarization, and pyroelectric properties were investigated systematically. The AFE to ferroelectric phase switching field E A‐F decreased with increasing x, while depolarization temperature T d increased with a linear relationship of T d = 842 x ‐483. Enhanced pyroelectric coefficient with a value of 12.1 μC/cm 2 /K was obtained at 88°C for the ceramics with x = 0.68, which was four times larger than the reported values. Composition‐dependent pyroelectric response over 24°C–140°C was realized by changing x from 0.60 to 0.74. The results also suggested that the enhanced pyroelectric response near T d was accompanied by a release of large P r, caused by an induced ferroelectric to AFE phase transition.